Indian Woods for Textile Mill Accessories - Part III. Jute Mill Rove Bobbins with 3-ply Ends (Evolved at the F.R.I.) - Rehman, M. A.; Askari, Mohd. (Indian Forester, 1956)
The Forest Research Institute, Dehra Dun has evolved a new type of bobbin with 3-ply ends which has been found very satisfactory with the added advantage that several second class woods can be used in this type of construction. 2. The main defect in the jute mill rove bohbins made of mango (Mangifera indica), haldu (Adina cordifolia), and kalam (Stephegyne parvifolia), the most commonly used Indian timbers for this type of bobbins, is the brittleness of the ends. As such the indigenous bobbins break more easily during handling in the mills than the imported bobbins made of birch and beech. One remedy to overcome this defect is the use of multi-ply ends. This would require elaborate plywood making machinery. In order to get over this difficulty an improved type of bobbin with 3-ply ends, referred to in para I has been evolved. 3. The paper describes the manufacturing details as well as the results of service tests carried out on this type of bobbins. These bobbins have been found very satisfactory and most of the big jute mill bobbin makers have switched on to this type of construction. Even in bobbins of smaller sizes the built-up construction using plies in place of single piece of solid wood for the ends is now preferred by most of the bobbin makers.